Fish and Fishery Products Analysis A Theoretical and Practical Perspective - Mathew, Saleena; Raman, Maya.; Kalarikkathara Parameswaran, Manjusha; Rajan, Dhanya Pulikkottil; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This novel and informative book discusses the various aspects of seafood quality. The book is divided into 7 broad sections, each tackling a different aspect. The first section covers the general aspects relevant to the nutritional quality of the fish and the various extraction protocols for macro-/ micro-nutrients. The second section provides insights into handling and the principles of thermal and non-thermal processing techniques for commercially important fishery products. The quality standards and safety concerns in the seafood industry and consumption are discussed in this section. The freshness indices of the processed products including biochemical, microbiological and toxicological characteristics are also included. The third section discusses the physico-chemical characteristics and quality parameters of potable water/ ice. The fourth section includes the quality assessment of various toxicants related to seafood products. The fifth section deals with the specific aspects such as principle, instrument and procedures of conventional and novel analytical instruments relevant to the seafood industry. The sixth section deals with the seafood waste management including solid and liquid seafood wastes. Presently, there is a great awareness regarding environmental sustainable processing/ preservation techniques. The final chapter discusses the bioactive compounds from under-utilized marine sources showing pharmaceutical/ nutraceutical applications.
Assessment of Nutritional Quality of Fish -- Fish and Fish Products: Quality Indices -- Water/ Ice: Assessment of Quality -- Toxicants: Assessment of Quality -- Techniques used in Fish and Fishery Products Analysis -- Waste Management in Seafood Industry -- Bioactive Compounds from Marine Sources.
Keywords: Food science; Nutrition .; Pharmacology; Food -- Microbiology; Biotechnology; Food Science; Nutrition; Pharmacology; Food Microbiology; Chemical Bioengineering